Ten years of seed production and establishment of regeneration measurements in Nothofagus antarctica forests under different crown cover and quality sites, in Southern Patagonia - Bahamonde, Héctor Alejandro (2018)
This study evaluated the seed production and quality and the subsequent regeneration establishment in five pure Nothofagus antarctica forests growing at different site qualities and crown cover during 10 years, in Southern Patagonia (Argentina). Four traps of 1 m2 were installed in each stand and sampled monthly (between February and May) each year. The incorporation and survival of seedlings were evaluated using four permanent plots of 1 m2 in each stand. The site quality of the studied forests did not influence seed production and regeneration. The amount of seed production and seed quality were proved to have a decisive influence on the N. antarctica seedling establishment in the subsequent years. At the same time, our results suggest that independently of the site class, the canopy openness for silvopastoral use improved the conditions for seedling establishment. However, the success of seedling survival over time would be conditioned for the influence of other factors such as understory competition.